Poly(HPMA)–chlorambucil conjugate nanoparticles: facile fabrication and in vitro anti-cancer activity. (27th September 2021) - Li, Guichen; Zhao, Minzhi; Zhang, Jia; Li, Haining; Xu, Weibing; Pu, Lumei; Shi, Xinhe
Abstract : An acid-sensitive poly(HPMA)–Chl conjugate was developed and its antitumor effect towards HepG2 and MCF-7 cells was evaluated. Abstract : Herein, the clinically approved nitrogen mustard, chlorambucil (Chl), is covalently embedded into a poly( N -(2-hydroxypropyl)methacrylamide, HPMA) vector via a hydrolysable ester bond to overcome the shortcomings of Chl as well as to achieve better efficacy. The well-defined poly-prodrug amphiphiles with Chl loading content >10 wt% can form uniform nanoparticles with an average diameter of 200 nm through a macromolecular self-assembly strategy. The detailed structure information and Chl release properties are carefully inspected. Cytotoxicity studies against the HepG2 and MCF-7 cell lines combined with flow cytometry reveal that the poly(HPMA)–Chl conjugate exhibits obvious targeting ability and markedly enhanced antitumor effect compared to the free Chl. After labelling with a fluorescent group, the cell uptake, lysosome escape and distribution in living organs of the poly-prodrug were also studied.